Continuous drawing of poly(ethylene terephthalate) in ethanol and agile functionalization through infusion. (June 2019) - Go, Dongwoo; Takarada, Wataru; Aneja, Arun; Kikutani, Takeshi
Abstract: To explore the possibility of applying organic-solvent drawing technique to accomplish a process of industrial significance, continuous drawing of as-spun PET fibers in ethanol was performed. The formation of multiple necks, infusion of ethanol into filament along with the uptake of dissolved dye was observed during the continuous drawing of PET filaments. The propagation speed of individual neck increased as the draw ratio increased, while effect of revolution speed of roller on the neck propagation speed was minimal because of the increase of the number density of neck along with the increase in processing speed. Through the monitoring of the drawing tension, it was found that the fluctuation of drawing tension is a source of instability of the drawing process. The installation of a drawing pin was discovered to be useful for the stabilization of the drawing process while increasing the amount of infused ethanol and dye uptake.